Case Study : Izara Cookies Sdn. Bhd. / Nurul Aini Mahmood - Mahmood, Nurul Aini (2020)
Mr. Mohd Razlil Ilahi established a company named Izara Cookies Sdn Bhd on 2011 that focuses on production of cookies. He had started the business in a small scale which was located at his home as well as opening a shop before expanding the company by opening a factory to largely produce and distribute more products to clients. Izara Cookies Sdn. Bhd. was opened in Kuala Lumpur and it is now located at Lot A-6 Kompleks Kilang SME BANK Kota Bharu 2, PT 5045 Kawasan Perindustrian Pengkalan Chepa, Fasa 2 Mukim Panchor Kemumin,16100, Kota Bharu, Kelantan with business registration number, P 1039227. The main activity of the business is to produce chocolate chip cookies with premium ingredients and could be eaten any time. Moreover, the owner had started the business with a modal of RM5000. It was used to buy a mixer and an oven as those were the most crucial machines for his new business. In 2020, the company has distributed their products to more than 1000 outlets in Malaysia while assisted by twenty workers. The vision of Izara Cookies Sdn. Bhd. is to become a cookies producing Bumiputera company that supplies halal and clean products that meet the standards of ISO22000. The main mission of this company is to be a dedicated Bumiputera cookies producer who makes high quality cookies for domestic and foreign market. The company targets to assist and give opportunities to other entrepreneurs to generate their own income as well as increase food products made in Malaysia in hypermarketssuch as Tesco, Giant and Jusco.